2021
DOI: 10.1109/mits.2020.2970180
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review Toward Decentralized Railway Traffic Management

Abstract: This paper analyses the literature to identify ideas which may be applied to decentralized real-time railway traffic management. This system represents a new way for dealing with railway traffic perturbations in absence of a central decision maker. Specifically, we are interested in identifying techniques that may constitute suitable automatic mechanisms for the emergence of an effective system behaviour. In this literature review, we discuss the possibility of exploiting the existing research works on other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 93 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…All problems which are at the same level in the decomposition can be coordinated in a direct exchange of information with each other (vertical communication). A recent, more extensive review on the topic of decentralized railway scheduling can be found in Marcelli and Pellegrini (2021). Such review includes also applications beyond railways, where decentralized solution methods have shown potential.…”
Section: Purely Decentralized Solution Methodsmentioning
confidence: 99%
“…All problems which are at the same level in the decomposition can be coordinated in a direct exchange of information with each other (vertical communication). A recent, more extensive review on the topic of decentralized railway scheduling can be found in Marcelli and Pellegrini (2021). Such review includes also applications beyond railways, where decentralized solution methods have shown potential.…”
Section: Purely Decentralized Solution Methodsmentioning
confidence: 99%
“…Some examples of decentralized decomposition are Brännlund, Lindberg, Nõu, & Nilsson (1998) ; Corman, D'Ariano, Pacciarelli, & Pranzo (2010) ; Luan, De Schutter, Meng, & Corman (2020) . A recent review can be found in Marcelli & Pellegrini (2021) .…”
Section: Decomposition In Railway Schedulingmentioning
confidence: 99%
“…Non-DLT solutions for WORM data storage include dedicated hardware 20 and software/cloud 21 designs, modifications of existing file systems 22 , or data archival 23 . Some database products support replication and "hot standby" / "cold standby" modes 24 , usually with a cluster-based distribution.…”
Section: Related Workmentioning
confidence: 99%
“…There are different approaches to build railway IT infrastructure in a more networked/peer-to-peer way. 38 However, none of them covers M2M payments and train-to-train economy.…”
mentioning
confidence: 99%